Deformation and fracture evolution of FeAl-based metallic-intermetallic laminate (MIL) composites. (1st August 2020) - Wang, Haoren; Zhu, Chaoyi; Vecchio, Kenneth S.
Abstract: FeAl-based Metallic-Intermetallic Laminate (MIL) composites exhibit enhanced strength and ductility compared to previously studied MIL composites. The deformation and fracture evolution of the FeAl-based MIL composites are investigated here via incremental compression testing. Microstructure assessment via electron backscatter diffraction suggests that deformation proceeds in a fairly homogeneous manner across gradients in the microstructure. Eventual failure is mainly induced by normal stresses, whereas other MIL composites typically fail by shear induced localizations. Geometrically necessary dislocation analysis indicates the FeAl regions deform in similar manners for the three MIL composites (Fe-FeAl-MIL, 430SS-FeAl-MIL, and 304SS-FeAl-MIL), and each fails in a similar mode. While the FeAl phase is the majority constituent of the composites, the mechanical properties are significantly influenced by the softer metal layers. The transition layer formed between the Fe-based metal layers and FeAl regions is the most critical constituent of the composites. Although the volume fraction of the transition layer is only ∼15%, a stronger transition layer can improve the work hardening behavior of the FeAl phase, increasing MIL composite strength by as much as 1 GPa. The findings can guide the design of the MIL composites to achieve even better mechanical properties. graphical abstract: